Influence of nitrogen, acid humic and nitrogen, phosphorus- soluble bacteria on saffron (Crocus sativus L.) corm reproduction and flower production of Torbat Heydarieh landrace - Ali Asghar Armak; Hassan Feizi; Masood Alipanah (علوم و فناوری بذر ایران)
With the aim of investigation of Humic and biological fertilizer sources together with nitrogen fertilizer on corm production on Torbat Heydarieh landrace, an experiment was conducted in research farm of University of Torbat Heydarieh in 2015-2016. The experiment consisted 18 treatments in which main factor was three levels of nitrogen fertilizer (0, 25, 50 kg/ha as urea) and sub factor was application of Biumic (micronutrients and acid humic), Super humic, Superhumic+Biumic, Humiful (acid humic), Nitrokara (nitrogen, phosphorus-soluble bacteria) and control. The experiment performed as split plot layout based on randomized complete block design with three replications. Results demonstrated that application of nitrogen had the significant effect on fresh weight and fresh yield of replacement corms. In 25 kg nitrogen treatment the fresh weight and fresh yield of replacement corms increased 5.6 and 8.2 percent in compared to control, respectively. In Super humic+Biumic treatment the fresh and dry weight of replacement corms increased 61.5 and 60.2 percent in compared to control, respectively. All of resource treatments significantly enhanced number of replacement corm. Overall, it seems that nitrogen fertilizer using had not considerable impact on corm traits, but employing of Humic and biological fertilizer could be very important on saffron corm production.